2022
DOI: 10.1101/2022.01.04.474801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving cassava bacterial blight resistance by editing the epigenome

Abstract: Pathogens rely on expression of host susceptibility (S) genes to promote infection and disease. As DNA methylation is an epigenetic modification that affects gene expression, blocking access to S genes through targeted methylation could increase disease resistance. Xanthomonas axonopodis pv. manihotis, the causal agent of cassava bacterial blight (CBB), uses transcription activator-like20 (TAL20) to induce expression of the S gene MeSWEET10a. We directed methylation to the TAL20 effector binding element within… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…However, these mutations often affect plant fitness with reduced growth, fertility, yield, and abiotic stress tolerance (Zaidi et al, 2018). Recently, Veley et al (2022) has been reported that directed methylation to EBE TALE20 region of MeSWEET10a promoter of TME419 in 60444 cassava cultivar, the plants displayed an increased resistance to Xam668 strain, meanwhile, they maintained normal growth and development (Veley et al, 2022). In our results, there were no significant differences in tuber root traits and starch content between the EBE TALE20 mutated lines and the wild type plants when grown under normal conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, these mutations often affect plant fitness with reduced growth, fertility, yield, and abiotic stress tolerance (Zaidi et al, 2018). Recently, Veley et al (2022) has been reported that directed methylation to EBE TALE20 region of MeSWEET10a promoter of TME419 in 60444 cassava cultivar, the plants displayed an increased resistance to Xam668 strain, meanwhile, they maintained normal growth and development (Veley et al, 2022). In our results, there were no significant differences in tuber root traits and starch content between the EBE TALE20 mutated lines and the wild type plants when grown under normal conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%